Investigation of vascular risk factor control and secondary prevention medication compliance in acute ischemic stroke - Chen, Yun; Zhang, Yuan; Jiang, Lianyan; Lu, Yanbin; Ding, Xiaojie; Jin, Wei; Xiong, Canxin; Huang, Daping (Frontiers in Neurology, 2024)
Objectives: This study aimed to investigate the management of vascular risk factors, with a specific focus on understanding the various factors affecting risk factor control through an in-depth analysis of clinical data and a longitudinal follow-up of patients who have experienced ischemic strokes.Methods: A total of 1572 participants were included in the analysis. We assessed thresholds for blood pressure (BP), low-density lipoprotein cholesterol (LDL-C), and glycated hemoglobin (HbA1c) levels to uncover the contextual conditions and factors affecting vascular risk factor control.Moreover, the study also scrutinized medication compliance at intervals of 3, 6, and 12 months postonset. Logistic regression was used to adjust for confounding factors.Results: At 3, 6, and 12 months, BP ,LDL, hemoglobin control targets were achieved in 50.7%, 51.8%, and 50.6%; 51.5%, 59.4%, and 50.6% ; 48.1%, 44.0%, and 48.4%,respectively. Notably, age was associated with the achievement of BP control (odds ratio [OR], 0.96; 95% confidence intervals [CI], 0.94-0.98; P <0.0001). Ethnic minorities (OR, 4.23; 95% CI, 1.19-15.09; P = 0.02) and individuals with coronary heart disease (OR, 0.5; 95% CI, 0.3-1.0; P = 0.05) experienced decreased BP control ratios. A previous history of stroke (OR, 1.7; 95% CI, 1.0-2.8; P = 0.03) and unrestricted alcohol consumption (OR, 3.3; 95% CI, 1.0-11.1; P = 0.05)was significantly associated with the achievement of lipid control. Furthermore, lifestyle modifications were significantly correlated with the achievement of BP control (OR, 0.19; 95% CI, 0.12-0.30; P <0.01), blood glucose control (OR, 0.03; 95% CI, 0.01-0.08; P <0.01), and blood lipid control (OR, 0.26; 95% CI, 0.16-0.42; P <0.01).The absence of regular physical activity was associated with lower rates of glycemic (OR, 0.14; 95% CI, 0.06-0.36; P <0.01) and lipid controls (OR, 0.55; 95% CI, 0.33-0.90; P = 0.01). Over time, overall medication compliance declined.Conclusion: Within the cohort of patients under medication, the compliance rate concerning vascular risk factors remains unsatisfactory. Attention should be paid to compliance with secondary prevention medications and enhance the control of vascular risk factors, as compliance emerges as the key to effective prevention.